Women’s Rights and Empowerment Movements in Nepal: A Study of Yogmaya and Seto Dharti - Gurung, Omi (JODEM: Journal of Language and Literature, 2025)
This article, “Women’s Rights and Empowerment Movements in Nepal: A Study of Yogmaya and Seto Dharti,” examines how Nepali literature responds to entrenched patriarchal structures that have historically curtailed women’s voices and denied them agency. Nepal’s socio-cultural history has been shaped by practices such as child marriage, enforced widowhood, polygamy, dowry, caste-based exclusion, and the Chhaupadi system, all of which silenced women and erased their subjectivities from official history. Literature, however, provides a vital counter-narrative that not only documents these hidden experiences but also resists oppressive traditions. The analysis focuses on two seminal Nepali novels; Neelam Karki Niharika’s Yogmaya and Amar Neupane’s Seto Dharti as feminist texts that illuminate both women’s suffering and their resilience. Yogmaya reconstructs the life of Yogmaya Neupane, a reformer whose personal defiance against patriarchal restrictions evolved into a collective movement challenging the Rana regime and caste–gender hierarchies. In contrast, Seto Dharti portrays the inner world of Tara, a child widow, whose gradual awareness of systemic injustice exemplifies a quieter but equally significant form of resistance. Employing radical feminism (Beauvoir; MacKinnon), intersectionality (Crenshaw), and feminist critique Rege, the article demonstrates how these narratives articulate women’s rights through both collective mobilization and individual resilience. Ultimately, “Women’s Rights and Empowerment Movements in Nepal: A Study of Yogmaya and Seto Dharti” underscores literature’s role as cultural testimony, a repository of marginalized voices, and a catalyst for envisioning gender justice in Nepal.